2012
DOI: 10.1128/aac.05191-11
|View full text |Cite
|
Sign up to set email alerts
|

Colistin-Resistant, Lipopolysaccharide-Deficient Acinetobacter baumannii Responds to Lipopolysaccharide Loss through Increased Expression of Genes Involved in the Synthesis and Transport of Lipoproteins, Phospholipids, and Poly-β-1,6- N -Acetylglucosamine

Abstract: We recently demonstrated that colistin resistance in Acinetobacter baumannii can result from mutational inactivation of genes essential for lipid A biosynthesis (Moffatt JH, et al., Antimicrob. Agents Chemother. 54:4971-4977). Consequently, strains harboring these mutations are unable to produce the major Gram-negative bacterial surface component, lipopolysaccharide (LPS). To understand how A. baumannii compensates for the lack of LPS, we compared the transcriptional profile of the A. baumannii type strain ATC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
154
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(179 citation statements)
references
References 56 publications
20
154
2
3
Order By: Relevance
“…Despite the fact that the Lol system is widely conserved across the gammaproteobacteria, activity was seen in only E. coli and H. influenzae. At present, it is not clear why cellular activity was not seen against a wider range of gammaproteobacteria, as the five Lol proteins are highly conserved across species (37), with the exception of Acinetobacter baumannii, for which no clear homolog of LolC has been identified (44). Some other clinically relevant gammaproteobacteria, such as P. aeruginosa, are notorious for their resistance to antibiotics due to the impermeability of their outer membranes and active efflux systems.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the fact that the Lol system is widely conserved across the gammaproteobacteria, activity was seen in only E. coli and H. influenzae. At present, it is not clear why cellular activity was not seen against a wider range of gammaproteobacteria, as the five Lol proteins are highly conserved across species (37), with the exception of Acinetobacter baumannii, for which no clear homolog of LolC has been identified (44). Some other clinically relevant gammaproteobacteria, such as P. aeruginosa, are notorious for their resistance to antibiotics due to the impermeability of their outer membranes and active efflux systems.…”
Section: Discussionmentioning
confidence: 97%
“…However, little is known about the regulation of Lol protein expression, although lipopolysaccharide-deficient Acinetobacter baumannii was very recently reported to exhibit increased expression levels of genes involved in lipoprotein trans- port, such as LolA, LolB, LolE, and LolD, to various extents (18). No clear homolog of LolC was identified in this gammaproteobacterium.…”
Section: Discussionmentioning
confidence: 99%
“…encode the genes for a T6SS, including Acinetobacter noscomialis and Acinetobacter baylyi, which possess a constitutively active antibacterial T6SS (20)(21)(22)(23)(24). A. baumannii strains have been shown by us and others to secrete Hcp (21,25), but to our knowledge a T6SS-dependent phenotype has not been ascribed to this species. Furthermore, our previous results showed that Hcp secretion is highly variable between A. baumannii strains, with some isolates carrying an inactive system (21).…”
mentioning
confidence: 99%